2013
DOI: 10.21897/rmvz.188
|View full text |Cite
|
Sign up to set email alerts
|

Determinación y prevalencia de Mycobacterium spp., en tilapia nilótica (Oreochromis niloticus) cultivada en Campeche, México

Abstract: RESUMENObjetivo. Determinar la presencia y prevalencia de Mycobacterium spp., en granjas de tilapia nilótica (Oreochromis niloticus) en el Municipio de Champotón, Campeche, México. Materiales y métodos. La colecta de organismos se realizó en tres granjas de cultivo de tilapia nilótica del municipio de Champotón, Campeche, México. Los organismos se examinaron externa e internamente y se tomó una muestra de riñón la cual fue sembrada en forma de estría en medios de cultivo: Löwesntein-Jensen, TCBS, KF y en TSA; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These strains were obtained from a previous study (Lara-Flores et al,2008), which determined the total population and groups of bacteria in Nile tilapia. The authors observed that the lactic acid bacteria were a minor part of microflora in Nile tilapia with less than 7% of the total count.…”
Section: Isolation and Identification Of Labmentioning
confidence: 99%
“…These strains were obtained from a previous study (Lara-Flores et al,2008), which determined the total population and groups of bacteria in Nile tilapia. The authors observed that the lactic acid bacteria were a minor part of microflora in Nile tilapia with less than 7% of the total count.…”
Section: Isolation and Identification Of Labmentioning
confidence: 99%
“…This microorganism is considered a potential pathogen for both tilapia and humans. In previous studies performed in Colombia (Pulido et al, 2004), Saudi-Arabia (Al-Harbi y Uddin, 2005), Cuba (Fuentes et al, 2011;Rubio-Limonta et al, 2010) and México (Lara-Flores et al, 2013), Streptococcus sp. was reported in tilapia.…”
Section: Discussionmentioning
confidence: 91%
“…A similar study in tilapia (samples of eye, brain, heart, spleen, liver, and kidney) from farms with intensive farming, during rainy and dry seasons, reported the detection of Streptococcus sp. in tilapia from the western, central and southern regions of Cuba in both seasons Lara- Flores et al (2013). reported a 13% prevalence of Streptococcus sp.…”
mentioning
confidence: 98%